Hirschev h- in m-kazalnik za napoved znanstvene kariere - Šercar, Tvrtko (Organizacija znanja, 2008)
In 2005, Hirsch developed the today commonly known and widely used h-index, the shortest quantitative indicator of the cumulative influence and relevance of the academic work of an individual researcher, a reseach group or an institution (university, institute, journal, etc.). The author reviews the results of selected studies on the options of a wider use of this indicator. The author emphasises the use of Hirsch's m-index for predicting an academic career, which has been overlooked in scientific literature so far.
Keywords: Hirschev h-index; Hirschev m-kazalnik; napovedovanje znanstvene kariere